Spelling Interventions for Elementary and Secondary Students with Learning Disabilities: A Systematic Review - Murnan, Reagan (Journal of the American Academy of Special Education Professionals, 2023)
Previous research investigating spelling interventions for students with learning disabilities (LD) are synthesized. A comprehensive search of the professional literature between 1990 and 2020 yielded a total of 19 elementary studies and 20 secondary intervention studies that delivered spelling interventions to students with LD and measured spelling outcomes. Additionally, this review of the research examines, journal outlets, intervention setting, intervention type, design, and outcome measures, related to the aforementioned spelling interventions. Findings revealed that the topic of spelling interventions for students with LD presents an ecological balance among journal outlets. Additionally, interventions employed, and measures used to assess spelling outcomes, were diverse among the elementary and secondary level. Implications and directions for future research are discussed.